Muslim minority in China: the case of Uyghur Muslims in Xinjiang - Fathil, Fauziah (2018)
Of the many minority Muslim groups in China, Uyghurs in Xinjiang Autonomous Region are currently being perceived by Beijing government as to have caused disunity in the country and involved in terrorist activities for which suppressive measures are warranted particularly since the Urumqi Riot in 2009. Consequently, the Uyghurs who belonged to Turkic ethnic group are prohibited among others from performing prayers in public, fasting during the month of Ramadhan for those in government service, growing beard for men below the age of fifty, etc. While the Beijing government argued that the measures are necessary in order to curb possible threats from the Uyghur population, the latter viewed that the restrictive rules are unjustified discrimination against the group. Using mainly content-analysis and library research methods, the paper will shed light on the history of the Uyghur community in Xinjiang, followed by their socio-economic and political conditions under the Chinese rule, and finally the contemporary situations in Xinjiang. Despite being the majority group in Xinjiang, due to several unwanted incidents in the province in recent years, the Uyghurs have gradually been deprived of their rights to practice Islam and lead Islamic lifestyle. The paper will thus assess the reasons behinds the increasingly stern Beijing policy towards the Uyghurs as well as the counter-reactions of the group towards such a policy.